Analisis Desain Formulir General Consent Rawat Inap (Studi Kasus di Lab RMIK Unjaya) - Kori Puspita Ningsih; Zakya Sinta Mahbubah (Lembaga Penerbitan Universitas Esa Unggul, 2021)
AbstractOne of the forms that show the patient's consent or the patient's family and is related to the patient's right to obtain health services in the hospital is general consent. This study aims to determine the general consent function of inpatients and to analyze the design of the general consent form from physical, anatomical, and content aspects. This research is a descriptive study, with a case study approach in the Laboratory of Medical Records and Health Information (D-3), Faculty of Health, Jenderal Achmad Yani University, Yogyakarta. The results showed that general consent was used as material for inpatient registration practice for students of the RMIK Study Program (D-3). This activity is carried out to achieve the competence of Medical Record Management, which is carried out by the roleplay method. The results of the analysis of general consent on the physical, anatomical, and content aspects show that it is necessary to redesign general consent on the anatomy and content aspects, including: (1) changes in the placement of items on gender and blood group (2) additional information on how to fill in the checklist form on the instruction placed at the top of the form, (3) confirmation of important information by giving a Bold sign, (4) the name and logo of the hospital is updated (5) the identity of the person in charge is completed with gender, place of birth date and name, while the address of the immediate family is deleted, (6) additional information related to patient rights and obligations and other witness signatures.Keyword: design analysis, general consent, inpatients AbstrakSatu diantara formulir yang menunjukkan persetujuan pasien atau keluarga pasien dan berkaitan dengan hak kewajiban pasien untuk memperoleh pelayanan kesehatan di rumah sakit adalah general consent. Penelitian ini bertujuan mengetahui fungsi general consent pasien rawat inap dan menganalisis desain formulir general consent dari aspek fisik, anatomi dan isi. Penelitian ini merupakan penelitian deskriptif, dengan pendekatan studi kasus di Laboratorium Rekam Medis dan Informasi Kesehatan (D-3) Fakultas Kesehatan Universitas Jenderal Achmad Yani Yogyakarta. Hasil penelitian menunjukkan general consent digunakan sebagai bahan praktik pendaftaran pasien rawat inap mahasiswa Program Studi RMIK (D-3). Kegiatan tersebut dilakukan mencapai kompetensi Manajemen Rekam Medis yang dilaksanakan dengan metode roleplay. Hasil analisis general consent pada aspek fisik, anatomi dan isi menunjukkan perlu dilakukan desain ulang general consent pada aspek anatomi dan isi meliputi: (1) perubahan pada penempatan item pada jenis kelamin dan golongan darah (2) penambahan informasi cara pengisian ceklist formulir pada instruction yang diletakkan di bagian atas formulir, (3) penegasan informasi penting dengan pemberian tanda Bold, (4) nama dan logo rumah sakit diperbaharui (5) identitas penanggungjawab dilengkapi dengan jenis kelamin, tempat tanggal lahir, dan nama sedangkan alamat keluarga terdekat dihapus, (6) penambahan informasi terkait hak dan kewajiban pasien dan penambahan tanda tangan saksi.Kata Kunci: analisis desain, general conset, rawat inap